Noninterference model for integrity - ZHANG Fan1; CHEN Shu2; SANG Yong-xuan1; YOU Lin1 (Tongxin xuebao)
The integrity noninterference model was investigated based on Rushby’s work.It was shown that the view-partitioned system and the reference monitor assumption-based system defined by Rushby still satisfy noninterfer-ence in the integrity condition as they do in the confidentiality condition;the integrity-noninterference explanation of the Biba model was given;the action-equivalence relation was proposed to deal with the integrity downgrading;two auto-matons,named the equivalent automaton and the purified equivalent automaton,were proposed to aid the noninterference deduction.